Comparison of calculated and experimental isotope edited FTIR difference spectra for purple bacterial photosynthetic reaction centers with different quinones incorporated into the QA binding site - Zhao, Nan; Lamichanne, Hari P.; Hastings, Gary (Frontiers in Plant Science, 2013)
Previously we have shown that ONIOM type (QM/MM) calculations can be used to simulate isotope edited FTIR difference spectra for neutral ubiquinone in the QA binding site in Rhodobacter sphaeroides photosynthetic reaction centers. Here we considerably extend upon this previous work by calculating isotope edited FTIR difference spectra for reaction centers with a variety of unlabeled and 18O labeled foreign quinones incorporated into the QA binding site. Isotope edited spectra were calculated for reaction centers with 2,3-dimethoxy-5,6-dimethyl-1,4-benzoquinone (MQ0), 2,3,5,6-tetramethyl-1,4-benzoquinone (duroquinone, DQ), and 2,3-dimethyl-l,4-naphthoquinone (DMNQ) incorporated, and compared to corresponding experimental spectra. The calculated and experimental spectra agree well, further demonstrating the utility and applicability of our ONIOM approach for calculating the vibrational properties of pigments in protein binding sites. The normal modes that contribute to the bands in the calculated spectra, their composition, frequency and intensity, and how these quantities are modified upon 18O labeling, are presented. This computed information leads to a new and more detailed understanding/interpretation of the experimental FTIR difference spectra. Hydrogen bonding to the carbonyl groups of the incorporated quinones is shown to be relatively weak. It is also shown that there is some asymmetry in hydrogen bonding, accounting for 10-13 cm-1 separation in the frequencies of the carbonyl vibrational modes of the incorporated quinones. The extent of asymmetry H-bonding could only be established by considering the spectra for various types of quinones incorporated into the QA binding site. The quinones listed above are “tail-less”. Spectra were also calculated for reaction centers with corresponding “tail” containing quinones incorporated, and it is found that replacement of the quinone methyl group by a phytyl or prenyl chain does not alter ONIOM calculated s